Síntese e propriedades da zeólita FAU com cristais nanométricos - Chaves, Thiago Faheina (2010)
The FAU zeolite was obtained using different amounts of water. Both at higher levels as the lowest amount of water the intensities of the diffraction peaks are less intense. The results of physisorption of these samples suggest the presence of material not yet crystallized in this product. The scanning micrographs show large spherical particles with apparent roughness, suggesting the formation of aggregates of smaller particles. For transmission electron microscopy the results show very dense clusters, with indicative that the particles are very cohesive. The crystallization curve shows that the stabilization of the phase occurs at 8 h of synthesis at 100 ° C, be interesting to work on shorter times to prevent the growth of particles. The aging of the mixture facilitated the crystallization of the material by decreasing the induction time and particle size. In high alkalinity can be observed a decrease in the intensity of diffraction peaks and size of particles observed by SEM. Long crystallization times produce materials with high external area, about 40% higher than a commercial sample. The variation of aging time of the samples with high alkalinity shows that with three days are obtained clusters of about 100 nm are formed by crystals even smaller. Therefore, was developed a method to obtain nanocrystals of zeolite FAU, without the presence of template and using silica and alumina sources with reduced cost.